(untitled) (Docentes 2.0 Journal, 2023)
Learning is an objective of education, whose process is part of acquiring theoretical and practical knowledge through the design and implementation of teaching-learning strategies, together with personal, social, and cultural experience. The research’s objective was to create a Virtual Learning Object (OVA) directed to the teaching-learning of the binary system. The research was based on the inductive method, positivist paradigm, quantitative approach, quasi-experimental design, exploratory type, and longitudinal cut. The OVA was presented to 15 students in the 8th semester of the Computer Engineering career at the Valle de Chalco University Center (CU) belonging to the Autonomous University of the State of Mexico (UAEMex). Satisfactory results were obtained in the questionnaire, which was applied to the students; they indicated that the OVA was to their liking, friendly, creative, and interactive, and they managed to acquire new knowledge or review the existing ones about the binary system.